(untitled) (LEARNing Landscapes, 2019)
This article investigates how playwriting served three middle school Black girls within a larger practitioner research study seeking to better understand the literate practices of girls of color. It delves into the ways that playwriting provided the girls in an afterschool writing club opportunities to explore both their knowledge and ways of knowing, rooted in their cultural, gendered, and racialized experiences, and, in turn, share these with others, within an academic setting. It points to the necessity for creating writing pedagogies that celebrate experiential, cultural, emotional, and relational knowledge, using playwriting as an example.